A constitucionalidade no ordenamento jurídico brasileiro, do decreto nº 5.144, de 16 de julho de 2004 - lei do abate de aeronaves - VIRISSIMO, Marcello Cristovão Guedes (2021)
The work presented here is an analytical study of the decree no. 5144, to July 16, 2004, which has normalized of Slaughter Act of Aircraft, Law no. 9614, to March 5, 1998, which established the legal possibility of shooting down civilian aircraft flying under the national territory, in violation of international rules on air traffic or refusing to provide their correct identification. The purpose of this study is to demonstrate the legitimacy, constitutionality and validity of that decree, before the constitutional principles, characteristics and purpose within the constitutional system. We tried to see how the right to protect state interests and the legal justification that allows the application of the slaughter of aircraft under international law, conflicts with the right to life protected by the Constitution of 1988. Furthermore, we analyzed the possibility of adopting the death penalty in Brazil to understand the essence of this decree, because the use of "shot of destruction" against aircraft during flight, in nearly all cases, determines the sentence of death everyone on board. Consideration was also the duty of government to protect its sovereignty and state power to exercise sanctions, observing the international conventions relating to the use of weapons for the killing of aircraft during flight. It demonstrates the intent of the decree regulating the identification, interception and killing of aircraft suspected of drug trafficking within the Brazilian airspace and the inability of the pilots of the Air Force Command being accused of criminal conduct. We analyzed the importance of the excluding unlawfulness, as far as our legal system, especially the strict performance of legal duty. Finally, we sought to demonstrate the State seeks to avoid the loss of human lives and the mechanism developed for the faithful performance of the "shot of destruction" that will fire only when they are exhausted all other legal procedures and possible attempts to avoid the trap needless deaths of innocent possible.